U.S. claims commissions records - United States. Spanish Treaty Claims Commission; United States. Board of Commissioners for the Adjustment of French Spoliation Claims
Miscellaneous records of the U.S. Board of Commissioners for the Adjustment of French Spoliation Claims and the U.S. Spanish Treaty Claims Commission.
Collection material in English, French, and Spanish.
Keywords: French spoliation claims; Spanish-American War, 1898 -- Claims